2016
DOI: 10.1016/j.cub.2016.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Termination of Protofilament Elongation by Eribulin Induces Lattice Defects that Promote Microtubule Catastrophes

Abstract: Microtubules are dynamic polymers built of tubulin dimers that attach in a head-to-tail fashion to form protofilaments, which further associate laterally to form a tube. Asynchronous elongation of individual protofilaments can potentially lead to an altered microtubule-end structure that promotes sudden depolymerization, termed catastrophe [1-4]. However, how the dynamics of individual protofilaments relates to overall growth persistence has remained unclear. Here, we used the microtubule targeting anti-cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
111
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 27 publications
13
111
0
2
Order By: Relevance
“…Noteworthy in this respect is our observation that when a MT continued growing after KIF21B was stalled, its growth was often strongly perturbed: we observed switching between growth and shortening episodes, as well as strong MT bending after the point of KIF21B attachment (Figure 7J). These data are reminiscent of our work on the effect of binding of a protofilament-blocking drug, Eribulin (Doodhi et al, 2016). We recently showed that attachment of a single Eribulin molecule, which, based on structural data can inhibit growth of only one MT protofilament, was sufficient to either cause a catastrophe or induce MT growth perturbation, suggesting elongation of an incomplete MT (Doodhi et al, 2016).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Noteworthy in this respect is our observation that when a MT continued growing after KIF21B was stalled, its growth was often strongly perturbed: we observed switching between growth and shortening episodes, as well as strong MT bending after the point of KIF21B attachment (Figure 7J). These data are reminiscent of our work on the effect of binding of a protofilament-blocking drug, Eribulin (Doodhi et al, 2016). We recently showed that attachment of a single Eribulin molecule, which, based on structural data can inhibit growth of only one MT protofilament, was sufficient to either cause a catastrophe or induce MT growth perturbation, suggesting elongation of an incomplete MT (Doodhi et al, 2016).…”
Section: Discussionmentioning
confidence: 56%
“…These data are reminiscent of our work on the effect of binding of a protofilament-blocking drug, Eribulin (Doodhi et al, 2016). We recently showed that attachment of a single Eribulin molecule, which, based on structural data can inhibit growth of only one MT protofilament, was sufficient to either cause a catastrophe or induce MT growth perturbation, suggesting elongation of an incomplete MT (Doodhi et al, 2016). It is tempting to speculate that similar to Eribulin, a KIF21B molecule stalled at the MT tip would be sufficient to block a small number of protofilaments, and this would result in inefficient elongation of the remaining protofilaments.…”
Section: Discussionmentioning
confidence: 56%
“…The second group including drugs such as vinca alkaloids and eribulin (a halichondrin) bind primarily to microtubule ends and are often referred to as microtubule destabilizers because at high concentrations, they block the addition of new tubulin subunits to microtubule ends, thus leading to microtubule depolymerization. However, their most potent activity is stabilization and inhibition of microtubule dynamic instability, which occurs with binding of low numbers of drug molecules at microtubule ends (7)(8)(9). Despite sharing the ability to suppress microtubule dynamic instability, we found that these two classes of drugs exert very different effects on microtubulebased transport.…”
Section: Introductionmentioning
confidence: 61%
“…5,[7][8][9]. The first group is sometimes referred to as microtubule stabilizers because by binding along the microtubule lattice, they stabilize microtubule dynamic instability and inhibit microtubule depolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…7 Eribulin (Figure 1), a simplified analog of halichondrin B, 8 binds within the vinca domain, and has unique effects on microtubule dynamics. 8,9 Structurally diverse natural products including rhizoxin and maytansine (Figure 1) bind to a different site on β-tubulin, referred to as the maytansine site. 10 The occupancy of this site by maytansine causes microtubule depolymerization by inhibiting longitudinal tubulin interactions.…”
mentioning
confidence: 99%